SMART CONTRACTS FOR FINANCIAL SECURITY: PROCESS AUTOMATION, RISK MITIGATION, AND ORGANIZATIONAL IMPLICATIONS - MARKOVIĆ, Svetlana; VLADISAVLJEVIĆ, Radovan; MARKOVIĆ, Marko (Journal of process management and new technologies, 2026)
Smart contracts are one of the most prevalent and important blockchain-based technologies in the field of financial security, as the automatic execution of predefined rules provides additional efficiency, lowers costs and minimizes the involvement of intermediaries. This research will examine the use of smart contracts for process automation, risk reduction and organizational restructuring in the financial sector. In particular, the interaction between centralized and decentralized financial systems, the technology behind the implementation of blockchain and security issues associated with the use of smart contracts will be considered. At the same time, escrows will be presented as an example of the practical use of smart contracts for financial operations. The results of this analysis will show that smart contracts can be used as a means to increase the reliability of financial operations; however, their widespread use depends on proper regulation, security assessment and integration with the existing financial infrastructure.